The urban computing on the distribution of inhalable particulate matters to Smart City–based residential groups. (24th August 2018) - Ma, Xi'na; Zhao, Jingyuan; Guo, Peng
Summary: Micro‐climatic factors have provided dynamic conditions and thermal conditions for the distribution of suspended particulate matters. In this paper, courtyard‐type residential clusters built in Xi'an were selected as the research objects, through field survey, spot test, and CFD analog simulation. Plane layout physical models of the various comparable courtyard‐type residential clusters were abstracted from the perspective of urban design, reasonable numerical models were established by field test and CFD simulation, and then simulation study was conducted to the plane forms of different courtyard‐type residential clusters; the influence of different forms on the dilution and spread of atmospheric pollutants was studied quantitatively. Finally, upon overall consideration over the turbulence characteristics in the vertical direction and the distribution law of pollutants under the influence of microclimate, it was concluded that the concentration of fine PM2.5 in the space of node‐type clusters in the plane layout of courtyard‐type clusters performed worst in the comparative scope, the most favorable form was U type clusters, and the available forms were windmill‐type clusters and scattered‐vertical type clusters.